Oddaljenost in bližina ljudskega v poeziji Alojza Gradnika - Pisk, Marjeta (Traditiones (Ljubljana), 2006)
The article examines the use of traditional folk song elements in the poetry of Alojz Gradnik. It focuses on the most prominent factors in the process of forming an identity, first as a child and later as an adult, and establishing a relation with one's birthplace. These represent important components in the poetry of Alojz Gradnik. Discussed are Gradnik's view of Medana, his home village, and of the local population, and the use of elements of folk poetry in his poems.
Keywords: Gradnik, Alojz, 1882-1967; slovenska poezija; etnologija; ethnology; identiteta; Ethnopoetics; ljudske pesmi; literarne študije